PROMOTION OF NUCLEAR ENERGY BY MEAN OF ANALYSIS OF NUCLEAR FUEL CONCENTRATION IF ACCIDENT OF PWR TYPE REACTOR OCCUR - (NIM: 20206027), SUKARNO
Public opinion regarding the nuclear energy is still misleading, especially if the reactor nuclear accident happens. Whenever the true information about the reactor accident can be desiminated in good ways to the public, their misperception may decreases significantly. Therefore, the public acceptance of nuclear energy may become increase. This manuscript aims to provide information concerning the nuclear energy through the analysis of nuclear fuel concentration if the accident of pressurized water reactor (PWR) occurs. The nuclear fuel concentration when the reactor accident depends on the half life and the initial concentration of nuclide in reactor. Nuclides that have short half life and large initial concentration will dominated the nuclear fuel concentration at the beginning of accident. A long time after the accident, the nuclear fuel concentration is strongly depended on the nuclide with the big half life and the high initial concentration. By employing the Delphi 7 language program and Runge-Kutta 4 method, the nuclear fuel concentration when the accident of PWR type reactor has been evaluated. The results show that As-91 has the highest concentration at 0-0.06 seconds after the accident. On the other hand at 0.06-1.25 second after the accident the concentration of Ge-89 is the largest one.